Identifying potential drugs for treating Cardiovascular-kidney metabolic syndrome via reverse network pharmacology - Wen, Si’ao; Fu, Ao’ni; Liu, Fen; You, Yayu; Li, Linkai; Xiao, Wen; Zhong, Haoran; Hong, Xiuqin; Zhong, Xin; Hu, Yongjun; Liu, Zhengyu (Frontiers in Pharmacology, 2025)
BackgroundCardiovascular, Kidney and metabolic syndrome (CKM) is a complex disease, for which current therapeutic approaches have limited efficacy. This study aims to screen for potential targets and novel drugs for treating CKM using network pharmacology.MethodsUsing reverse network pharmacology, core targets and potential drugs for CKM were identified. Candidate compounds were screened from a natural product library. Male C57BL/6J mice were fed a high-fat L-NAME diet for 12 weeks to induce CKM and confirm successful model establishment, followed by 4 weeks of BBR (Berberine) treatment. Metabolic parameters, as well as cardiac and renal structural and functional indices, were assessed. Key targets and potential drugs identified through network pharmacology and bioinformatics were validated using pathological analysis, RT-qPCR, and Western blotting (WB), collectively demonstrating the therapeutic effects of BBR on CKM.ResultsNetwork pharmacology identified multiple core targets of CKM, and reverse pharmacology discovered the potential drug BBR (Berberine) from a natural product library. In vivo experiments demonstrated that the “two-hit” HFpEF model, which is induced by a high-fat diet combined with L-NAME treatment for 12 weeks and is characterized by metabolic disorders, cardiac diastolic dysfunction, and renal fibrosis, can be used as a new model of CKM. BBR improved metabolic disorders, cardiac diastolic function, and renal damage in CKM mice by regulating lipid metabolism, glucose metabolism, and fibrosis-related pathways.ConclusionThe “two-hit” HFPEF model can be used as a new model of CKM, and BBR may become a new candidate drug for the treatment of CKM through multiple targets.